An analytical study of the common and unique characteristics of local studies centers in Central Luzon and CALABARZON regions - Perez, Martin Julius V. (2011)
This study aimed to provide an overview and, at the same time, define and describe the common and unique characteristics, practices and status of local studies centers in Central Luzon Region (Region 3), and CALABARZON Region (Region 4a) of the Philippines. This study is intended to be a source of ideas and guidelines for the establishment of local studies centers in the future. It is in this light that this study focused on the mandates, structural characteristics, linkages, programs/services, programs/services beneficiaries, and management group's perceived extent of utilization of the five local studies centers in the two regions: Batangas Heritage Center (BHC), Cavite Studies Center (CSC), Center for Bulacan Studies (CBS) (Bahay-saliksikan ng Bulacan), Center for Central Luzon Studies (CCLS) and the Juan D. Nepomuceno Center for Kapampangan Studies (CKS).